Reading aloud listening test items to young learners: Attention, item understanding, and test performance. (August 2022) - Hui, Bronson; Wong, Sharon Sin Ying; Au, Ricky K.C.
Abstract: In second language (L2) listening assessment for young learners, test items are often read aloud by the narrator or by the teacher administering the test. Although read-alouds seem to be a special test feature for children, a solid empirical basis of this practice has not been established in the literature. In this article, we examine the relationship between read-alouds, test takers' attention, perceived item understanding, and test performance. We report an experiment where non-native English-speaking children completed a baseline reading test before taking a sample TOEFL Primary listening test on an eye tracker in two conditions: items fully read aloud (FRA) and items partially read aloud (PRA). After each item, test takers also rated their understanding of the item. We found that the read-alouds helped in drawing test takers' attention to the corresponding written information on the screen. However, no robust differences were found in perceived item understanding, and test performance was equivalent between the two conditions. We discuss the implications for test administrators on assessment design for this population.